Quantitative correlation of rock fragment gradation parameters and TBM disc cutter efficiency: Insights from DEM simulations - Jiawei An; Qianlong Wang; Jianxing Liao; Chaolin Wang; Yachen Xie; Yiqiang Lu; Fei He; Dabin Zhang (PLoS ONE, 2026)
This study explores the relationship between rock fragment size distribution and disc cutter breaking efficiency of a tunnel boring machine (TBM) using discrete element simulations of indentation tests. Fragmentation behavior was analyzed under varying joint dip angles, joint spacings, and confining pressures, and cutter efficiency was evaluated by correlating fragment gradation parameters with specific energy (SE). The results show that cracks preferentially propagate along the weak joint interfaces, demonstrating that joint geometry controls stress redistribution and fracture evolution. With increasing joint dip angle, crack density and crushed zone extent first increase and then decrease. Reduced joint spacing enhances crack interaction and coalescence, resulting in lower energy demand. In contrast, increasing confining pressure suppresses tensile crack development, restricts crack opening displacement, and promotes shear-dominated failure, leading to finer fragments and higher SE. Strong linear correlations (R² > 0.80) between gradation parameters and SE indicate that fragment size distribution quantitatively reflects variations in energy dissipation during cutter and rock interaction.